The Increasing Importance of Developing Countries in Trade in Services - Sáez, Sebastián (World Bank, Washington, DC, 2012)
Services play a broad and strategic role in the economy. The new focus in services arises because they have become increasingly tradable, allowing for the emergence of new and improved export activities. Trade in services, particularly business services, has become a dynamic component of trade and an alternative for export diversification for many developing countries. Besides traditional activities (such as tourism), health, information technology, and communication services are among the most successful service exports. Developing countries seem to follow different policy approaches to trade in services, and diverse trade patterns appear to emerge. What determines the participation of a developing country in trade in services? And what is the role of international negotiations?